Optimizing Method for Potato Meristem Vitrification - Shevchenko, Nadiya; Stribul, Tamara; Rozanov, Leonid (Probl Cryobiol Cryomed, 2005)
Comparative data of potato meristem cryopreservation according to different freezing protocols are shown. The possibility to vary conditions for apexes (shoot-tips) preparing to cryopreservation using vitrification method was investigated. There was proposed a vitrification PVSN solution with modified composition. A possibility to exclude some steps of preliminary meristem preparing to freezing with no loss in integrity of cryopreserved material was established.
Stribul TF, Shevchenko NA, Rozanov LF. Optimizing Method for Potato Meristem Vitrification. Probl Cryobiol Cryomed. 2005. 15(4): 657–664.
Keywords: cryopreservation; vitrification; meristem; potato; vitrifying solution